EFFORTS TO STEM RADICALISM AT THE NURUSSALAM ISLAMIC BOARDING SCHOOL - Halid, Ahmad; Bin Jali, Hasan; Alif Rohmatullah Kusasih, Gusti; Arifin, Syamsul; Ardy Ansyah (MAJEMUK Jurnal Pendidikan Agama Islam, 2025)
This article examines deradicalization and violence in education: A study of Islamic education analysis based on the treasures of Madrasah-Pesantren at the Pesantren Nurussalam. This research method uses a qualitative-descriptive method. Data collection techniques use observation, interview and documentation methods. Data validity uses data triangulation by comparing the research results of experts with more than three opinions. Data analysis in this study uses disciplined inquiry and reality and uses a content analysis model. The very interesting findings of this study about the very effective Deradicalization of pesantren are (1) the kiai teaches noble ethics to all students accompanied by the provision of examples from the kiai. (2) the kiai teaches yellow books written by the group of defenders of Islam Ahlussunnah wal Jama’ah, a moderate group in Islam (3) checks the books written before being taught to all students with the aim of avoiding books written by experts in heresy, radical heretics (4) the kiai teaches love for the Indonesian homeland as a legacy of the struggle for independence of the Indonesian nation and the pesantren community (5) the thoughts taught to the students are tawassuth, I’tidal, tawazun, tasamuh, tabayyun, amar makruf nahi mungkar (Halid 2023) (6) local Indonesian culture with friendliness (7) peace, mutual respect, preserving local pesantren traditions (8). Understanding Islam from original sources and schools of thought, conducting ijtihad. With these eight, pesantren produce students who are humanist and have Islamic morals rahmatan lin alamin